2014
DOI: 10.1148/radiol.14132269
|View full text |Cite
|
Sign up to set email alerts
|

Matched within-Patient Cohort Study of Transient Arterial Phase Respiratory Motion–related Artifact in MR Imaging of the Liver: Gadoxetate Disodium versus Gadobenate Dimeglumine

Abstract: Fixed off-label dose (10 or 20 mL) of gadoxetate disodium is associated with arterial phase respiratory motion-related artifact that is sometimes severe and occurs significantly more often than after gadobenate dimeglumine in patients who received both contrast media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
113
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 13 publications
10
113
1
1
Order By: Relevance
“…Davenport et al demonstrated that gadoxetate disodiumassociated TSM is more frequent (15 %) after application of a fixed dose of 20 ml compared to a fixed dose of 10 ml (10 %) [24]. Other studies, however, were not able to confirm a dose-dependent relationship of gadoxetate disodium and TSM [8,10,12].…”
Section: Influence Of Contrast Dosementioning
confidence: 98%
See 1 more Smart Citation
“…Davenport et al demonstrated that gadoxetate disodiumassociated TSM is more frequent (15 %) after application of a fixed dose of 20 ml compared to a fixed dose of 10 ml (10 %) [24]. Other studies, however, were not able to confirm a dose-dependent relationship of gadoxetate disodium and TSM [8,10,12].…”
Section: Influence Of Contrast Dosementioning
confidence: 98%
“…Regarding age, Shah et al found that the risk of arterial phase motion artifacts increases with age [14], but none of the other groups confirmed a predisposition of higher age towards TSM [15,24].…”
Section: Potential Individual Risk Factorsmentioning
confidence: 98%
“…4 In addition, the use of gadoxetic acid itself has been reported to result in degraded arterial phase images compared with that using extracellular contrast media, thereby hindering accurate lesion characterization. 57 Until now, there have been ample reports documenting “transient dyspnea” or “transient severe motion” frequently occurring after gadoxetic acid administration, although the specific mechanism is not yet fully understood. However, recent studies have shown that the reported incidence based on retrospective image reviews or subjective symptoms 5,6,8 may not reflect the actual incidence.…”
mentioning
confidence: 99%
“…However, even after 2 years passed from the first report, this phenomenon has been only reported from United States. [1][2][3] At least, it was not observed in the recent study from Japan which is about gadolinium-based contrast agents-related adverse events in large cohort. 4 I also met some radiologists who even doubted the occurrence of dyspnea, because they had not encountered such cases.…”
mentioning
confidence: 94%
“…Severe motion-related artifacts during the arterial phase were observed in approximately 18% 2 or 10% 3 of patients in whom gadoxetic acid was injected. However, even after 2 years passed from the first report, this phenomenon has been only reported from United States.…”
mentioning
confidence: 99%